Harnessing AI for Enhanced Weather Prediction: A Focus on Rainfall - Hira Farman; Noman Islam; Noman Hasany (JISR on Computing)
Natural distasters such as landslides, heat waves, storms, tsunamis, floods, earthquakes, and droughts endanger the lives of thousands of people worldwide. Flooding is one of the most catastrophic difficulties that natural catastrophes may cause. It has serious consequences, including growing death rates, health issues, and economic deadlock. These are all the outcomes of the circumstance. Flooding is one of the effects of excessive rainfall, demonstrating the need of precisely forecasting the quantity of rainfall that will fall. Existing models may struggle to reflect the dynamic and complicated character of meteorological systems, making it challenging to build effective flood protection techniques and predict accurate rainfall. The abstract simply outlines the paper’s goal of constructing a durable rainfall prediction model based on a single classifier and the stacking method. The paper uses historical weather data ranging from 2000 to 2023, and the data source includes different regions in Pakistan. The goal is to maximize the level of predicted events to include rainfall cases. The primary objective of study is to design and evaluate single and combine machine learning models, a stacking approach to forecast rainfall in Pakistan. The study will compare the accuracy and reliability of SCADA ((Supervisory Control and Data Acquisition) to the benchmark for the specific area in question which will reveal the best prediction method. The stacking model method seemed to be less optimal as the results derived from it were not as satisfactory as the ones achieved by the individual modelsAmong all the algorithms experimented with in this work, the best one was AdaBoost. It had an Area Under the Curve (AUC) of 0.999 and almost 99% classification accuracy of the results. It was nearly as good as the others at distinguishing between rainy and dry, according to the recall and F1 scores, which were between 0.95 and 0.999.Further, K-Nearest Neighbors (kNN) also produced excellent results, specifically in terms of AUC, where the algorithm achieved 0.941, as well as precision with a score of 0.817. In the final analysis, these developments may lead to improved methods for disaster preparedness and mitigation, lessening the destructive effects of floods on areas that are already at risk.